Responsibilities of Notaries/PPAT in Ensuring Legal Certainty Regarding The Delivery of Land Rights Certificates by Developers to Buyers - Prameswari, Kintan Kartika; Hafidz, Jawade (TABELLIUS: Journal of Law, 2025)
Abstract. This study examines the responsibilities of Notaries and Land Deed Officials (PPAT) in ensuring legal certainty regarding the transfer of land title certificates by developers to buyers. Problems often arise when developers fail to hand over certificates even though buyers have fully paid their obligations, thus creating legal uncertainty and harming consumers. This study uses a normative juridical method with a statute approach. Data were obtained through literature review and analyzed qualitatively using descriptive-analytical methods. The results show that Notaries/PPATs have the responsibility to ensure that the deeds they make meet formal and material requirements, and play a preventive role in protecting buyers' rights. Therefore, strengthening regulations and oversight mechanisms is needed to ensure legal certainty.Keywords: Certificate; Developer; Legal Certainty; Notary; PPAT.